The earl's Egyptian heiress - Helmy, Heba (Harlequin historicals., 2023)
"Ranya Radwan's mission is clear: restore her family's honor by retrieving the deed to their business from the Earl of Warrington. Until she finds herself enthralled by the new earl, Owen. Accompanying him from Egypt to England to find the deed, Ranya's swept into an unfamiliar world of society balls and luncheons, but is captivated waltzing in Owen's arms. Yet her duty to her family means returning to Egypt, not following her heart..."--